Determine Environmental Structure Condition of River Sub System of Palembang City’s Rivers using Geospatial Analysis - Usman, Fathoni; Hamim, Sumi Amariena (International Journal of Engineering and Technology, 2018)
This paper present geospatial analysis to determine the environmental structure of the river sub-system of Palembang City where 70% of the city is located at lowland with elevation from 0 to 5 m above mean sea level. This lowland terrain condition induced problem of water puddle and flood during a rainfall event. A landscape ecological approach and spatial analysis approach of river sub system (RSS) morphometry characteristic were conducted to determine the environmental structure condition of the RSS. The data used to generate the DEM was the height data obtained from the map of the city line on a scale of 1:1000 with stereophotogrammetric digital technique. The line map contains spot height data made every 20 m distance in the field. From this study, new delineation of RSS boundaries was produced and gave different catchment areas. It is found that the perimeter of the RSS and the mean value of bifurcation ratio determined the value of runoff in the RSS.